ESTIMATION OF THE BEST LINEAR UNBIASED PREDUCTION (BLUP) OF RAMS DEPENDING ON THEIR PROGENY'S BIRTH AND WEANING WEIGHT - & et al., Raoof (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted in a private sheep herd at Kurdistan region- Iraq during the period from June/2015 to Augest/2016. A total of 189 ewes and 9 rams were used and aimed to study the effect of some non-genetic factors (age of dam,sex and type of birth, estrous sequences cycle and ewes weights at lambing ) on the birth and weaning weights. The heritability  and the best liear unbiased preduction (BLUP) were estimated. The overall means of the birth and weaning weights were 3.90 and 24.25 kg respectively.The results showed that the birth weight and weaning weight were significantly ( p